Effect of Breed on Slaughter and Carcass Characteristics of Adult Male Chickens - Pal, U.K.; Mandal, P.K.; Rao, V. Kesava; Das, C.D.; Venugopal , S. (Journal of Meat Science, 2011)
An experiment was conducted to study the effect of breed on slaughter characteristics, cut-up parts, meat, bone and skin yield of adult male birds. Twenty seven male birds of about one year age belonging to four breeds namely Australorp (4), Naked Neck (8), White Cornish (5) and White Leghorn (10) maintained in the college farm were slaughtered in the Department of Livestock Products Technology and the data were collected and analysed. White Cornish birds recorded significantly higher (P<0.05) live weight compared to Naked Neck, Australorp and White Leghorn breeds. Similar trends were observed for carcass, meat and bone yield on weight basis for different breeds and these differences were significant (P<0.05) except between Australorp and White Leghorn. When expressed as percentage of live weight dressed carcass yield recorded to be lowest in White Leghorn followed by Australorp, Naked Neck and White Cornish. Among the cut-up parts, back contributed highest followed by breast, thigh, drumstick, wings and neck to the carcass weight in all the three breeds except White Cornish in which breast was the highest contribu tor. Yield (%) of back and drumstick varied significantly (P<0.05) among the breeds, whereas, yield (%) of other cut-up parts did not show any significant variation. Naked Neck breed yielded significantly lower (P<0.05) amount of skin compared to White Cornish. All the carcasses were almost devoid of separable fat. Based on the data it was concluded that White Cornish males were producers of higher quantity of carcass, meat and bone with lower amount of inedible by-products followed by Naked Neck, Australorp and White Leghorn, respectively.